Prevalence, Virulence Genes, Antimicrobial Susceptibility, and Genetic Diversity of Bacillus cereus Isolated From Pasteurized Milk in China - Gao, Tiantian; Ding, Yu; Wu, Qingping; Wang, Juan; Zhang, Jumei; Yu, Shubo; Yu, Pengfei; Liu, Chengcheng; Kong, Li; Feng, Zhao; Chen, Moutong; Wu, Shi; et al. (Frontiers in Microbiology, 2018)
Bacillus cereus is a common and important food-borne pathogen that can be found in various food products. Due to low-temperature sterilization for a short period of time, pasteurization is not sufficient for complete elimination of B. cereus in milk, thereby cause severe economic loss and food safety problems. It is therefore of paramount importance to perform risk assessment of B. cereus in pasteurized milk. In this study, we isolated B. cereus from pasteurized milk samples in different regions of China, and evaluated the contamination situation, existence of virulence genes, antibiotic resistance profile and genetic polymorphism of B. cereus isolates. Intriguingly, 70 samples (27%) were found to be contaminated by B. cereus and the average contamination level was 111 MPN/g. The distribution of virulence genes was assessed towards 10 enterotoxigenic genes (hblA, hblC, hblD, nheA, nheB, nheC, cytK, entFM, bceT and hlyII) and one emetic gene (cesB). Forty five percent strains harbored enterotoxigenic genes hblACD and 93% isolates contained nheABC gene cluster. The positive rate of cytK, entFM, bceT, hlyII and cesB genes were 73%, 96%, 75%, 54% and 5%, respectively. Antibiotic susceptibility assessment showed that most of the isolates were resistant to β-lactam antibiotics and rifampicin, but susceptible to other antibiotics such as ciprofloxacin, gentamicin and chloramphenicol. Total multidrug-resistant population was about 34%. In addition, B. cereus isolates in pasteurized milk showed a high genetic diversity. In conclusion, our findings provide the first reference on the prevalence, contamination level and characteristics of B. cereus isolated from pasteurized milk in China, suggesting a potential high risk of B. cereus to public health and dairy industry.